Adsorption Characteristics of Three Types of Soils on Biogas Slurry Ammonium Nitrogen - Wang, Zichen; Zhang, Liping; Sun, Guofeng; Zhou, Wei; Sheng, Jing; Ye, Xiaomei; Olaniran, Ademola O.; Kana, E. B. Gueguim (Frontiers in Environmental Science, 2022)
Using farmland to digest biogas slurry is an effective measure to overcome the bottleneck of sewage treatment in livestock and poultry farms. However, there is little research on the soil adsorption characteristics of biogas slurry ammonium nitrogen (NH4+-N). In addition, the adsorption capacity (Qm) of farm soil is unclear. In this study, three typical farmland tillage layer soils (silty loam, loam, and sandy loam) were used to analyze the adsorption characteristics through adsorption kinetics and thermodynamic experiments. The value of Qm was fitted by models, and its relationship with soil properties is discussed. The results showed the following: (1) the adsorption of biogas slurry NH4+-N by the three types of soils was a composite kinetic process that comprised two stages of rapid and slow reactions. The fast adsorption predominantly occurred within 0–1 h, and the adsorption capacity accounted for 35.24–43.55% of the total adsorption. The ExpAssoc equation produced good fit for the adsorption kinetic behavior in the three types of soils. (2) The equilibrium adsorption could be described by the Langmuir equation, Freundlich equation, the PlPlatt model, and the Langevin model isotherm, among which the Langevin model had the best fit, with a coefficient of determination R2 being close to 1. The theoretical saturated Qm fitting results of NH4+-N were 1038.41–1372.44 mg/kg in silty loam, 840.85–1157.60 mg/kg in loam, and 412.33–481.85 mg/kg in sandy loam. The optimal values were 1108.55 mg/kg, 874.86 mg/kg, and 448.35 mg/kg for silty loam, loam, and sandy loam, respectively. (3) The value of Qm was significantly positively correlated with soil organic matter, total nitrogen, available phosphorus, available potassium, cation exchange capacity, and particle content of 0.02–0.002 mm (P< 0.01) but significantly negatively correlated with soil pH (P< 0.05). This study can provide a reference for the safe application of biogas slurry on farmland.